Thermally induced changes of broad contact pulse-operated single quantum well (SQW) separate confinement heterostructure (SCH) laser spectra - Kowalczyk, Emil; Ornoch, Leszek; Szerling, Anna; Mroziewicz, Bohdan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
A technique of time-resolved laser spectra mapping has been developed to assess thermo-optical properties of diode lasers. Using this technique the emission spectra of broad contact pulse operated diode lasers were measured for consecutive time points within the pulse duration width. The emitted wavelength was found to be highly dependent on the time elapsing from the pulse front and a time shift of wavelength was clearly observed in the spectrum of pulse-operated lasers.
Optica Applicata, Vol. 35, 2005, nr 3, s. 573-578
Keywords: optyka; thermal dynamics; SQW laser; spectrum